2016
DOI: 10.1088/1009-0630/18/4/17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Precleaning on the Plasma Treatment Efficiency of Aluminum by RF Plasma Pencil

Abstract: This paper is aimed to show the influence of initial chemical pretreatment prior to subsequent plasma activation of aluminum surfaces. The results of our study showed that the state of the topmost surface layer (i.e. the surface morphology and chemical groups) of plasma modified aluminum significantly depends on the chemical precleaning. Commonly used chemicals (isopropanol, trichlorethane, solution of NaOH in deionized water) were used as precleaning agents. The plasma treatments were done using a radio frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Many researchers have reported that the physical characteristics of films can be altered via the usage of plasma treatment procedures [17][18][19][20][21][22][23]. Plasma treatment is a procedure that changes the material's surface, leading to a change in roughness [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many researchers have reported that the physical characteristics of films can be altered via the usage of plasma treatment procedures [17][18][19][20][21][22][23]. Plasma treatment is a procedure that changes the material's surface, leading to a change in roughness [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that the physical characteristics of films can be altered via the usage of plasma treatment procedures [17][18][19][20][21][22][23]. Plasma treatment is a procedure that changes the material's surface, leading to a change in roughness [17][18][19][20][21][22]. Plasma ions can chemically react with the film's surface and can also physically bombard some particles or contaminant from the surface, both resulting in the modification of the surface and wetting properties, including an improvement of film surface quality [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations